Strategi Adaptasi Mahasiswa Asing UNS dalam Upaya Mengatasi Gegar Budaya di Solo - Meysty Yurianti; Sigit Pranawa; Yuhastina Yuhastina (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
The purpose of this study was to determine UNS foreign students adaptation strategies when overcoming cultural shock. The research method is qualitative with a descriptive approach, iIn determining the informant used purposive sampling technique. Sources of data used here are primary source and secondary source. Data were collected through interviews, observations, and documentation. Source triangulation and method triangulation were used to get a valid data. Data were analyzed using the intercultural adaptation theory by Yong Yun Kim, to look for adaptation strategies undertaken by foreign students in facing culture shock. The findings of the data show that foreign students experience the phenomenon of culture shock and go through several phases including planning, honeymoon, frustration, readjustment and resolution. Foreign students found several obstacles as their survival challenges including communication, type of food, religious life, use of language, stereotypes, customs, weather and climate, facilities and services, and education system. The conclusion of this research is there are five adaptation strategies undertaken by foreign students namely; personal communication, host social communication, ethnic social communication, environment and predisposition.